Effects of exchanged ammonium cations on structure characteristics and CO2 adsorption capacities of bentonite clay - Elkhalifah, A.E.I. (2013)
Different alkali and alkaline earth cation forms of bentonite clay were exchanged with protonated mono-, di- and triethanolamine compounds, to study the effect of the exchanged ammonium cations on the structure characteristics, thermal behavior, surface properties and CO2 adsorption capacities of bentonite clay. The revolution of the interlayer structure characteristics, thermal properties, the specific surface area and elemental analysis were characterized by XRD, FTIR, TGA, BET and CHNS techniques respectively, while the CO2 adsorption capacities were gravimetrically measured by using magnetic suspension balance (MSB) equipment. It was found that the intercalation of ammonium cations into the interlayer space of bentonite clay induced a step change in its basal spacing, depending on their molar mass and the interlayer molecular arrangement. The presence of the characteristic IR peaks of amine compounds in the spectra of bentonite clay adsorbents modified by amines was qualitatively supported by the incorporation of ammonium cations in the interlayer space of bentonite, while the presence of C, H and N elements using CHNS technique was quantitatively confirmed by the intercalation process of amine compounds. It was also found that the molar mass of amines has an inverse effect on the amount of the adsorbed water (intensity), its desorption temperature (position) and the specific surface area of the synthesized materials. The CO2 adsorption capacities on all the studied bentonite clay adsorbents modified by amines were found to increase between 2.68 and 3.15mmol/g, compared to 0.93mmol/g for untreated bentonite at the studied temperature and pressure. As expected, bentonite clay modified with di- and triethanolammonium cations showed lower CO2 adsorption capacities than that treated with monoethanolammonium cations, due to their low specific surface area. Â© 2013 Elsevier B.V.